Rancang Bangun Sistem Aplikasi Amaliyah Tarekat Qadiriyah Naqsabandiyah (TQN) Suryalaya Berbasis Android - Maulana Hasan Mud’is; Hasan Mud’is (Institut Teknologi Garut, 2023)
The rapid development of technology today has become a primary need in society, one of which is a system for practicing a series of amaliyah worship in people who believe in the Suryalaya Qadiriyah Naqsabandiyah Order (TQN), while there is still a lot of amaliyah data that has not been computerized in data collection resulting in laziness to carried anywhere and is not effective for memorizing the amaliyah of the Qadiriyah Naqsabandiyah Order (TQN) Suryalaya. This application is a murshid amaliyah learning application which consists of daily dhikr, khataman, manaqiban and styles of the Koran letters which are often read during fardhu prayers, so that people can make it easier to read and memorize the practice of the tarekat qadiriyah naqsabandiyah (TQN) Suryalaya anywhere, the application it was designed with android studio using the java programming language with blackbox testing. The research was conducted by collecting data through literature and interviews. This research produced an amaliyah mursyid application for the Suryalaya Qadiriyah Naqsabandiyah (TQN) congregation along with practices, styles of the Qur'an and Manaqiban recitation locations using Google Maps. This application is expected to make it easier for the congregation or the community of the Qadiriyah Naqsabandiyah (TQN) Suryalaya order to read and memorize the practices of the murshid.